Effect of Nile tilapia (Oreochromis niloticus) on the growth performance of Pacific white shrimp (Litopenaeus vannamei) in a sequential polyculture system - Hernández-Barraza,Cesar (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2012)
The present study was carried out at the Environmental Research Laboratory (ERL), University of Arizona, to assess the effect of the addition of Nile tilapia (Oreochromis niloticus), at different densities, on the growth performance of Pacific white shrimp (Litopenaeus vannamei). The growth rate and feed conversion of shrimp, both in polyculture and monoculture, were evaluated. Shrimp-tilapia proportions were 20:8 individuals in Treatment One (T1), 20:4 individuals in Treatment Two (T2) and 20:2 individuals in Treatment Three (T3), while in Treatment Four (T4) shrimp were stocked as a control group with a ratio of 20:0. The experiment lasted for four weeks at 10 ppt water salinity. The shrimp and fish were fed once a day with 8% and 3% of their body weight, respectively, using a 35% protein feed. At the end of the experiment, the average individual weight and best feed conversion ratio were obtained in shrimp polyculture treatment with highest tilapia density 6.08 ± 0.18 g and 1.26 ± 0.01 respectively, while the lowest scores were found in the monoculture treatment with 5.14 ± 0.59 g and 1.35 ± 0.01, respectively (P < 0.05). The present study demonstrate that integrated farming of shrimp and tilapia, with a polyculture sequential tanks system is technically feasible and increases the production of shrimp, which is higher than in monoculture, without any adverse interaction between fish and shrimp.